2011
DOI: 10.1200/jop.2010.000076
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Adherence and Persistence With Oral Medications for Cancer Treatment

Abstract: Novartis, East Hanover, NJ As oral cancer therapies are developed, a high degree of persistence and adherence is necessary for optimal outcomes. Ensuring persistence, continuing treatment for the prescribed duration, and adherence-taking medication as prescribedhas been a challenge to patient management and health care cost containment in real-world settings. 1 It may appear as though persistence and adherence to oral cancer therapies is superior to that observed with oral noncancer therapies. 2 Indeed, patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…However, dosing and adherence to these treatments outside of the clinical trial setting has not been well studied, and may be lower than that in clinical trials. 9 Having a better understanding of such outcomes may help oncologists and payers to make more informed decisions regarding treatment choices and reimbursement of these medicines. [10][11][12] The primary objective of the current study was to estimate medication persistence and compliance (adherence) among patients with advanced RCC receiving pazopanib as first-line therapy or after previous treatment with ≥ 1 other therapies outside the clinical trial setting.…”
Section: Study Sample Selectionmentioning
confidence: 99%
“…However, dosing and adherence to these treatments outside of the clinical trial setting has not been well studied, and may be lower than that in clinical trials. 9 Having a better understanding of such outcomes may help oncologists and payers to make more informed decisions regarding treatment choices and reimbursement of these medicines. [10][11][12] The primary objective of the current study was to estimate medication persistence and compliance (adherence) among patients with advanced RCC receiving pazopanib as first-line therapy or after previous treatment with ≥ 1 other therapies outside the clinical trial setting.…”
Section: Study Sample Selectionmentioning
confidence: 99%
“…However, patients require active physician participation in guiding their decision to take oral versus intravenous therapy, and most patients attribute their preference for oral chemotherapy to convenience and problems linked to intravenous access. Despite optimal adherence and persistence are a necessary prerequisite to achieve the best possible clinical outcome, clinical research has shown that a significant percentage of patients report suboptimal adherence, which may be even far lower in the real-word populations outside of clinical trials [83]. Poor adherence has also a negative reflex on medical costs and may increase the use of medical resources.…”
Section: Expert Opinionmentioning
confidence: 95%
“…While oral agents pose many notable advantages when compared to conventional parenteral drugs, including enhanced convenience of self‐administration, reduced hospital and societal costs, and improved patient engagement in their own care 1, 2, 3, 4, these benefits must be balanced against growing concerns regarding poor compliance to treatment and its potentially negative impact on outcomes 1, 2, 3, 4, 5, 6. Suboptimal adherence to medications is a commonly recognized problem for many chronic medical conditions, such as hypertension and diabetes mellitus, where it has been shown to compromise drug effectiveness 7, 8, 9, 10.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies on medication compliance in oncology have focused on oral hormonal therapies in breast cancer 5, 6, 11, 12, 13 even though oral drugs are also frequently used in other cancers 14, 15, 16, 17. In colon cancer, the oral 5‐fluorouracil prodrug known as capecitabine is a commonly prescribed component in a large number of systemic therapy regimens 18, 19, but it has received relatively little focus to date 20, 21, 22, 23.…”
Section: Introductionmentioning
confidence: 99%